UMPSA develops Strategic Plan 2026-2030 (UMPSA30) - Rosidah, Hassan (UMPSA, 2025)
KUANTAN, 7 March 2025 – The Centre for Strategic & Quality Management (PPSK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), has conducted a series of workshops to develop the UMPSA Strategic Plan 2026-2030 (UMPSA30) at Grand Darulmakmur Hotel. The two-day workshop aimed to outline the university’s strategic direction for the next five years.